Implementing the Brainstorming Technique to Improve Students’ Ability in Writing Descriptive Text (An Action Research to the Seventh-Grade Students at SMPIT Albina Kota Ternate) - Fatma Kaufua (English Education Department, Faculty of Education Muhammadiyah University of North Maluku, 2021)
This research aims at improving the skill of writing descriptive texts through brainstorming technique for the seventh-grade students at SMPIT Al-Bina Kota Ternate. This classroom action research was initiated from the students' results in writing descriptive tests using the brainstorming technique, which consisted of two cycles. The researchers implemented the actions in the class. The qualitative data was obtained by the writing test results from 22 students in the seventh-grade grade at SMPIT Al-Bina Kota Ternate. This study showed that the brainstorming technique in the writing class was believed to be adequate to enhance students’ ability in writing descriptive texts. It was shown from the results of students writing descriptive text in cycle 1 and cycle 2. Students' writing scores improved from 68.50 in cycle 1 to 84.18 in cycle 2. In addition, the brainstorming technique helped the students to generate ideas and organize them into paragraphs. As a result, they could manage the time for writing more effectively and perform the writing task more maximally. This activity implies that implementing the brainstorming technique in the writing instructions positively affects students’ performance and achievement in writing descriptive text. Brainstorming helps the students to activate their prior thought before practicing their writings. Keywords: brainstorming, students’ ability, descriptive text